pH- and temperature-sensitive, injectable, biodegradable block copolymer hydrogels as carriers for paclitaxel - Shim, Woo Sun; Kim, Jong-Ho; Kim, Kwangmeyung; Kim, Yoo-Shin; Park, Rang-Woon; Kim, In-San; Kwon, Ick Chan; Lee, Doo Sung (ELSEVIER SCIENCE BV, 2007)
Paclitaxel (PTX) was loaded into synthetic pH/T-sensitive block copolymer (OSM-PCLA-PEG-PCLA-OSM) solution with various concentrations. The phase diagram of PTX-loaded block copolymer solution shifted to lower temperature region compared to net block copolymer because of the salting-out effect of PTX. Release profiles of PTX showed sustained manner regardless of loading amount of PTX. To evaluate anti-tumor effect of PTX-loaded block copolymer, solutions were injected subcutaneously to tumor-bearing mice and TUNEL assay examined. PTX-loaded block copolymer hydrogel for in vivo use showed good anti-tumor effect for 2 weeks and induced strong apoptosis in tumor tissue. Therefore, we conclude OSM-PCLA-PEG-PCLA-OSM block copolymer as an effective injectable carrier of PTX (c) 2006 Elsevier B.V. All rights reserved.
Keywords: CONTROLLED-RELEASE; TRIBLOCK COPOLYMER; DELIVERY-SYSTEM; DRUG-RELEASE; FORMULATION; TAXOL; PLGA; ACID; METASTASES; LIPOSOMES